PEDAGOGICAL CONDITIONS FOR THE EFFECTIVE ORGANIZATION OF LESSONS IN INCLUSIVE PRIMARY SCHOOL CLASSES - Rakhimova D.A.; Elmuradova S.Х. (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
The article is devoted to the study of the pedagogical conditions necessary for the successful organization of the educational process in inclusive primary school classrooms. It examines the main methods and technologies that help create a supportive educational environment for all students, including children with special educational needs. The author analyzes the principles of differentiated and individual approaches, the importance of the role of teachers and assistants, as well as the use of modern educational tools. Special attention is paid to the development of an inclusive culture in schools and the improvement of the professional training of teachers.